Strain modulation of magnetic coupling in the metallic van der waals magnet Fe3GeTe2. (April 2021) - Zhu, Mengmei; You, Yurong; Xu, Guizhou; Tang, Jiaxuan; Gong, Yuanyuan; Xu, Feng
Abstract: We investigated the strain modulation of the magnetic states and interatomic exchange interactions in layered van der Waals magnet Fe3 GeTe2 by detailed first-principles studies. The energy-minimum calculations demonstrate the ground state of bulk Fe3 GeTe2 is weak antiferromagnetic coupling, in contrast to most precious reports, and it can be modulated to ferromagnetic coupling under small a -axis distortion ( 2%). More importantly, we obtained the variation of exchange coupling parameters J ij and Curie temperature TC under both uniaxial and isotropic strain, and found the TC can be enhanced to room temperature in the case of uniaxial lattice distortion, especially along the a -axis. Our work clarified the role of intra- and inter-layer magnetic coupling in tuning of the ground state magnetism that can be generally applied in two-dimensional layered materials and suggested a paradigm for tuning TC with uniaxial strain in Fe3 GeTe2 . Highlights: The ground state of Fe3 GeTe2 can be tuned from antiferromagnetic to ferromagnetic coupling under small a -axis distortion ( 2%). The interatomic magnetic coupling in bulk Fe3 GeTe2 is systematically studied and discussed. The Curie temperature of Fe3 GeTe2 can be enhanced to room temperature under a -axis distortion.